Resolusi Konflik Rumah Tangga: Upaya Mitigasi Tingginya Kasus Perceraian di Probolinggo - Yakin, Ainul; Syauqi, Ahmad Farid (Universitas Nurul Jadid, 2024)
The high divorce rate in Probolinggo presents significant social and cultural challenges, leading to issues such as juvenile delinquency, school dropouts, and family instability. This study investigates the factors contributing to household conflicts and explores strategies for mitigating divorce cases in Sidopokso Village, Kraksaan, Probolinggo. Utilizing a qualitative phenomenological approach, data were collected through interviews, observations, and documentation. The findings indicate that third-party involvement (50%), domestic violence (10%), and economic issues (20%) are the primary triggers of divorce. The normalization of divorce as a solution to family conflicts reflects limited understanding and application of Islamic principles in household management. This study recommends educational programs to promote harmonious family environments, economic resilience through employment opportunities, and support for at-risk families. Addressing these factors is critical to reducing divorce rates and strengthening family stability.